LITERATURE STUDY: VALIDITY AND RELIABILITY TEST OF MASLACH INSTRUMENTS BURNOUT INVENTORY-HUMAN SERVICES SURVEY (MBI-HSS) IN NURSES IN SEVERAL COUNTRIES - Liza Fauzia; Kadek Ayu Erika; Andi Masyitha Irwan (Journal of Nursing Science Update (JNSU), 2019)
Burnout Syndrome is one of the most vulnerable psychological problems occurring in nurses in hospitals. The incidence of burnout syndrom in nurses, if it is allowed to be untreated specifically, it will affect on work productivity, physical and psychological disorders. Therefore, it is important to identify nurses who are at risk in developing the burnout syndrome. To identify this, a valid and reliable instrument is needed so that the data obtained is accurate. The aim of this study literature was to identify the value of the validity and reliability of the Maslach Burnout Inventory-Human Service Survey (MBI-HSS) instrument in several countries in measuring burnout syndrome of nurse. The databases used in this literature study were PubMED, Science Direct and Google Schoolar. There were 21 articles identified and published from 2010-2017. Of the 21 articles, 5 articles met the inclusion criteria. The results showed that the value of validity and reliability were good enough, from the results of the validity test, the three-factor analysis was considered the best analysis among the other factor analyzes that produced acceptable model fit values and items that had a validity value below the standard were 20 items (deleted items12 and 16), Lebanon 20 items (deleted items 13 and 22), Sri Lanka 21 items (deleted item 4), South Africa 20 items (deleted items 4 and 6), and France 17 items (deleted 12,16,6,22,13) while the reliability of the MBIHSS instrument in some countries shows the reliable value with cronbach alpha > 0.70. In conclusion the value of validity and reliability of the instrument shows the accuracy in collecting data. With the value of validity and reliability of the MBI-HSS instrument, it is expected to help practitioners and other researchers in identifying the accuracy of the MBI-HSS instrument in measuring the burnout syndrome of nurses.